2022
DOI: 10.1111/liv.15403
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of COVID‐19 vaccines in chronic liver disease patients and liver transplant recipients: A systematic review and meta‐analysis

Abstract: Background and aims Chronic liver disease (CLD) patients and liver transplant (LT) recipients have an increased risk of morbidity and mortality from coronavirus disease 2019 (COVID‐19). The immunogenicity of COVID‐19 vaccines in CLD patients and LT recipients is poorly understood. The present study aimed to evaluate the immunogenicity of COVID‐19 vaccines in CLD patients and LT recipients. Methods We searched electronic databases for eligible studies. Two reviewers inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 51 publications
(328 reference statements)
2
22
0
Order By: Relevance
“…14,15,[52][53][54] This meta-analysis included 17 controlled studies for effectiveness analysis and six studies for safety analysis. It was found that SARS-CoV-2 vaccines are safe and well-tolerated in patients with CLD and post-LT, while exhibiting lower pooled seropositivity rates of antibodies to vaccination, especially post-LT patients, compared with that of the healthy population; these results are consistent with those of Luo et al 55 When compared with the patients with CLD, the pooled seropositivity rates of antibodies to SARS-CoV-2 were lower in LT recipients. Moreover, this meta-analysis found that the antibody-positive rate after the booster dose increased by 27% compared with that of the standard vaccination regimen.…”
Section: Safety Of Sars-cov-2 Vaccinessupporting
confidence: 86%
“…14,15,[52][53][54] This meta-analysis included 17 controlled studies for effectiveness analysis and six studies for safety analysis. It was found that SARS-CoV-2 vaccines are safe and well-tolerated in patients with CLD and post-LT, while exhibiting lower pooled seropositivity rates of antibodies to vaccination, especially post-LT patients, compared with that of the healthy population; these results are consistent with those of Luo et al 55 When compared with the patients with CLD, the pooled seropositivity rates of antibodies to SARS-CoV-2 were lower in LT recipients. Moreover, this meta-analysis found that the antibody-positive rate after the booster dose increased by 27% compared with that of the standard vaccination regimen.…”
Section: Safety Of Sars-cov-2 Vaccinessupporting
confidence: 86%
“…A recent meta-analysis demonstrated that seroconversion rates seem to be similar in patients with CLD compared with healthy individuals except for LTR 103. However, the antibody responses seem to be generally weaker.…”
Section: Sars-cov-2 and The Adaptive Immune Responsementioning
confidence: 99%
“…6,44 A systematic review and meta-analysis of 19 studies including 1700 LT recipients, 1624 patients with CLD, and more than 800 healthy controls compared pooled rates of detectable humoral immune response to SARS-CoV-2 vaccination and found no difference between patients with CLD and healthy controls, or between cirrhotic and non-cirrhotic patients. 45 The study found that immune response depended on vaccine type, with two doses of mRNA vaccine yielding positive humoral immune response in 99% of patients with CLD, compared to 91% in those who received inactivated vaccines. 45 In studies evaluating spike-specific T-cell response to vaccination, on the other hand, patients with CLD had a significantly lower response than healthy controls, but a significantly greater response than LT recipients.…”
Section: Covid-19 Prevention In Patients With Cld and Ltmentioning
confidence: 95%
“…45 The study found that immune response depended on vaccine type, with two doses of mRNA vaccine yielding positive humoral immune response in 99% of patients with CLD, compared to 91% in those who received inactivated vaccines. 45 In studies evaluating spike-specific T-cell response to vaccination, on the other hand, patients with CLD had a significantly lower response than healthy controls, but a significantly greater response than LT recipients. 7 Therefore, it has been posited that despite comparable antibody seroconversion rates, ineffective T-cell response may result in decreased protection from SARS-CoV-2 in patients with CLD and LT compared to healthy controls.…”
Section: Covid-19 Prevention In Patients With Cld and Ltmentioning
confidence: 95%